From training activities to a training program: a case study in animal research - Harrison, Jerricka D. (Kansas State University, 2024)
Within an animal research facility, the customers include the organization (who benefits from the successful conduct of research procedures), the trainees (who benefit from the use of those skills to maintain their job or advance their career), and the animals, who benefits from humane and proficient care by animal users. Animal use training programs must be designed to meet the unique and interconnected needs of all three of these customers to achieve success. Adequate training of personnel involved in the care and use of animals is not only vital to the success of a research program, but also required by law within the United States and many other countries. An inadequate training program can lead to deficiencies in animal care and use, which can cause the research institution to face government citations, fines, loss of accreditation status, loss of grants or business, delays in project deliverables, decreased employee morale, negative media reports, and adverse public attention. American Biotech Company is an organization which develops and manufactures pharmaceuticals, vaccines, diagnostic test kits, and other biomedical devices. As such, the use of animals in research is a critical component to its success. The company’s Animal Care and Use Department (ACUD) is responsible for managing all animals used in its research and development (R&D) initiatives. In recent years, the company has encountered numerous challenges such as mitigating changes in the regulatory landscape, supporting changing research portfolios and business objectives, and adapting to an evolving workforce. These challenges have exposed deficiencies and risks in the way the department conducts animal use training. Currently, there is no systematic oversight of training activities within the ACUD. The existence of silos between groups has led to inconsistency in training resulting in portfolio support constraints and difficulties sharing people resources across teams and worksites. Gaps in the facilitation of knowledge transfer and the lack of clear training guide points have contributed to a “drift” in processes. The inefficient management of training databases, content, and records within the department has contributed to a chronic overdue training phenomenon, rendering many employees “out of compliance” with regulatory or corporate standards and limiting scheduling capabilities. The absence of a unified training program has also negatively impacted employee engagement and limited the ability of the department to assess skills and training activities and apply appropriate improvement strategies when needed. The overall purpose of this thesis is to propose the implementation of a comprehensive training program that will position the ACUD to overcome the current challenges and mitigate the risks to animal use training within the department. Development of this program will require a thorough characterization of the internal (organizational background, attributes and current conditions) and external (regulations/legislation, accreditation standards, and industry recommendations) influences, and identification of recommended tools and methods, in order to answer the question: How will development and implementation of the proposed training program address the deficiencies and risks associated with the ACUD’s animal use training activities? The proposed comprehensive training program can address the needs of its customers by supporting four key success pillars: 1) Performance, 2) Compliance, 3) Engagement, and 4) Assessment/Continuous Improvement. Designating a training manager and developing the strategic direction for the program will ensure that performance, compliance, and engagement needs, risks, and trends are consistently assessed and mitigated across all groups and worksites within the department. The implementation of a core training team is key to optimizing training capabilities, as it will allow training experts to execute training activities according to newly established standards while offering dynamic learning opportunities to meet the needs of a wide range of employees. Standardization of training processes, expectations, and information will ensure the ACUD is meeting its regulatory obligations. And by proactively supporting professional development and continued learning, the department can increase retention of highly skilled, motivated, and compassionate animal users. This comprehensive approach will better equip American Biotech Company to continue developing products that support the health and wellness of its customers and the proposed tools have the potential to support innovation and sustainability throughout the animal research and welfare industry as a whole.
Keywords: Training; Animal use; Change management; Animal research; Training management